Early parasympathetic dysfunction in Parkinson’s disease: insights from information-theoretic analysis - Cernanova Krohova, Jana; Oleksakova, Jana; Turianikova, Zuzana; Czippelova, Barbora; Grofik, Milan; Kurca, Egon; Javorka, Michal (Frontiers in Network Physiology, 2025)
IntroductionParasympathetic nervous system (PNS) dysfunction in Parkinson’s disease (PD) has been frequently evaluated using heart rate variability (HRV) analysis in the time and frequency domains. Findings across studies have been inconsistent, limiting a unified understanding of early autonomic impairment.MethodsIn this study, we applied both conventional and advanced analytical methods to evaluate cardiovascular PNS function in the early-stage PD patients. Sixteen individuals with PD (<6 months after motor signs occurrence) and sixteen age- and sex-matched healthy controls were assessed across three protocol phases (supine rest, head-up tilt, and supine recovery). Traditional HRV analysis in the high-frequency band was used to estimate the overall respiratory heart rate variability (RespHRV; updated and more appropriate term for the respiration-related heart rate oscillations formerly called respiratory sinus arrhythmia, RSA) magnitude. To distinguish between baroreflex-mediated and non-baroreflex RespHRV mechanisms, we employed multiscale Partial Information Decomposition (PID), an information-theoretic method. Cardiac baroreflex sensitivity (BRS), reflecting reflex parasympathetic control, was assessed using a causal estimation approach, further supported by a PID-derived parameter quantifying coupling between systolic arterial pressure and R-R intervals. Additionally, the presence of constipation – a clinically relevant non-motor symptom indicative of parasympathetic dysfunction was used to stratify the PD cohort.ResultsEarly-stage PD patients exhibited signs of parasympathetic impairment, particularly during orthostatic stress. HRV analysis showed reduced HF power during head-up tilt, while causal BRS was significantly lower across all protocol phases in the PD group. PID analysis further demonstrated a significant reduction in baroreflex-mediated mechanism of RespHRV during head-up tilt in PD patients compared with healthy controls, indicating early dysfunction of the cardiac chronotropic baroreflex. This impairment was more pronounced in the group with gastrointestinal issues (with the presence of constipation).DiscussionThese findings support the α-Synuclein Origin site and Connectome model, which proposes that PD patients whose neurodegeneration originates in the peripheral autonomic nervous system are characterized by early and more severe autonomic dysfunction.